23. Rozwiąż nierówności: a) (3x – 2) ^ 2 – 5x – (3x + 2)(3x – 2) < (2 - 3x) ^ 2 - 9x ^ 2 + 4 b) c) d) 2 * (x - 3) ^ 2 - 1/2 >= ((2x – 3)(2x + 3))/2 – x (x – 3) ^ 2 – (x ^ 2 – 3)/3 – 9 < ((x - 2)(x + 2))/6 + 1/2 * x ^ 2 1 - (3x - 2) ^ 2 >= (x – 36)/3 – 9(x + 1) * (x – 1)

23. Rozwiąż nierówności: a) (3x – 2) ^ 2 – 5x – (3x + 2)(3x – 2) < (2 – 3x) ^ 2 – 9x ^ 2 + 4 b) c) d) 2 * (x – 3) ^ 2 – 1/2 >= ((2x – 3)(2x + 3))/2 – x (x – 3) ^ 2 – (x ^ 2 – 3)/3 – 9 < ((x – 2)(x + 2))/6 + 1/2 * x ^ 2 1 – (3x – 2) ^ 2 >= (x – 36)/3 – 9(x + 1) * (x – 1)